Functional integration of a semi-synthetic azido-queuosine derivative into translation and a tRNA modification circuit. Issue 18 (28th September 2022) - Bessler, Larissa; Kaur, Navpreet; Vogt, Lea-Marie; Flemmich, Laurin; Siebenaller, Carmen; Winz, Marie-Luise; Tuorto, Francesca; Micura, Ronald; Ehrenhofer-Murray, Ann E; Helm, Mark
Abstract: Substitution of the queuine nucleobase precursor preQ1 by an azide-containing derivative (azido-propyl-preQ1 ) led to incorporation of this clickable chemical entity into tRNA via transglycosylation in vitro as well as in vivo in Escherichia coli, Schizosaccharomyces pombe and human cells. The resulting semi-synthetic RNA modification, here termed Q-L1, was present in tRNAs on actively translating ribosomes, indicating functional integration into aminoacylation and recruitment to the ribosome. The azide moiety of Q-L1 facilitates analytics via click conjugation of a fluorescent dye, or of biotin for affinity purification. Combining the latter with RNAseq showed that TGT maintained its native tRNA substrate specificity in S . pombe cells. The semi-synthetic tRNA modification Q-L1 was also functional in tRNA maturation, in effectively replacing the natural queuosine in its stimulation of further modification of tRNA Asp with 5-methylcytosine at position 38 by the tRNA methyltransferase Dnmt2 in S. pombe . This is the first demonstrated in vivo integration of a synthetic moiety into an RNA modification circuit, where one RNA modification stimulates another. In summary, the scarcity of queuosinylation sites in cellular RNA, makes our synthetic q/Q system a 'minimally invasive' system for placement of a non-natural, clickable nucleobase within the total cellular RNA.